Gaya Kepemimpinan KH. Abdullah Al-Faqir dalam Membangun Kemandirian Ekonomi Pondok Pesantren Mambaul Khairat - Riduansyah, Riduansyah; Firayanti, Yuni; Marhamah (ECONOMETRICS:Journal of Sustainable Economics and Management, 2025)
This research aims to analyze the leadership style of KH. Abdullah Al-Faqir in building economic independence at Pondok Pesantren Mambaul Khairat, Ketapang Regency, West Kalimantan. A qualitative approach was used with techniques such as interviews, observations, and documentation to obtain primary and secondary data. Data analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing. The validity of the data was tested using source triangulation techniques and methods to ensure the credibility of the research results. The research results show that the leadership style of KH. Abdullah Al-Faqir is a combination of charismatic, democratic, and transformational. This leadership is able to build the loyalty of students, management, and the community, as well as empower students in managing business units. The strategy for economic independence is achieved through the arrangement of human resources based on competence, deliberation, financial transparency, and internal-external synergy. These findings affirm that adaptive and participatory charismatic leadership can serve as a model for other Islamic boarding schools in building sustainable economic independence.